Silver-Catalyzed One-Pot Biarylamination of Quinones with Arylamines: Access to N-Arylamine-Functionalized p-Iminoquinone Derivatives - Dong, Yu; Jiang, Hui; Chen, Xiang-Long; Ye, Ji-Xian; Zhou, Qiang; Gao, Long-Sen; Luo, Qi-Qi; Shi, Zhi-Chuan; Li, Zhong-Hui; He, Bing (Synthesis, 2022)
Concise one-pot biarylamination of quinones with arylamines was developed to synthesize N-arylamine-functionalized p-iminoquinones derivatives. The approach employed AgOAc as the catalyst and (NH4)2S2O8 as the oxidant in the presence of 3-chlorophenylboronic acid, giving a series of N-arylamine-functionalized p-iminoquinone derivatives in moderate to good yields whereas reaction in the absence of the 3-chlorophenylboronic acid, gave a series of N-arylamine-functionalized 1,4-naphthoquinone derivatives. This catalytic approach represents a step-economic and convenient strategy for the difunctionalization of quinones.
Keywords: silver-catalyzed; biarylamination; quinones; arylamines; N-arylamine-functionalized p-iminoquinones